Public budget composition, fiscal (de)centralization and welfare - Calin Arcalean; Gerhard Glomm; Ioana Schiopu; Jens Suedekum (Institute for the Study of Labor (IZA), 2007)
We present a dynamic two-region model with overlapping generations. There are two types of public expenditure, education and infrastructure funding, and governments decide optimally on budget size (tax rate) and its allocation across the two outlays. Productivity of government infrastructure spending can differ across regions. This assumption follows well established empirical evidence, and highlights regional heterogeneity in a previously unexplored dimension. We study the implications of three different fiscal regimes for capital accumulation and aggregate national welfare. Full centralization of revenue and expenditure decisions is the optimal fiscal arrangement for the country when infrastructure spending productivity is similar across regions. When regional differences exist but are not too large, the partial centralization regime is optimal where the federal government sets a common tax rate, but allows the regional governments to decide on the budget composition. Only when the differences are sufficiently large does full decentralization become the optimal regime. National steady state output is instead highest when the economy is decentralized. This result is consistent with the Oates conjecture that fiscal decentralization increases capital accumulation. However, in terms of welfare this result can be reversed
urn:nbn:de:101:1-20080416382
Keywords: 330; Finanzföderalismus; Infrastrukturinvestition; Produktivität; Regionale Entwicklung; Wohlfahrtseffekt; Zentralstaat; Dezentralisierung; Theorie